2021 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2021
DOI: 10.23919/date51398.2021.9474000
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Silicon-Photonic Neural Networks under Uncertainties

Abstract: Silicon-photonic neural networks (SPNNs) offer substantial improvements in computing speed and energy efficiency compared to their digital electronic counterparts. However, the energy efficiency and accuracy of SPNNs are highly impacted by uncertainties that arise from fabrication-process and thermal variations. In this paper, we present the first comprehensive and hierarchical study on the impact of random uncertainties on the classification accuracy of a Mach-Zehnder Interferometer (MZI)based SPNN. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…While several high-performance AI accelerators based on coherent SP-NNs have been recently proposed [2,10,13], [14] showed that the inferencing accuracy of SP-NNs can drop by up to 70% due to fabrication-process variations and thermal crosstalk. In addition to these variations, the work in [10] explored the impact of optical loss non-uniformity among MZIs and showed SP-NN performance degradation.…”
Section: Related Prior Workmentioning
confidence: 99%
See 2 more Smart Citations
“…While several high-performance AI accelerators based on coherent SP-NNs have been recently proposed [2,10,13], [14] showed that the inferencing accuracy of SP-NNs can drop by up to 70% due to fabrication-process variations and thermal crosstalk. In addition to these variations, the work in [10] explored the impact of optical loss non-uniformity among MZIs and showed SP-NN performance degradation.…”
Section: Related Prior Workmentioning
confidence: 99%
“…1(a)), where the number of MZIs depends on the OIU architecture [6]. Note that šœƒ and šœ™ in each MZI, where šœƒ determines the state and hence optical loss and crosstalk noise introduced in each MZI, depend on the weight parameters and can be determined using SP-NN training algorithms [14]. The output of the OIU is connected to an optical-gain unit (OGU) that includes semiconductor optical amplifiers (SOAs) [7].…”
Section: Layer-level Compact Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, any deviations in such adjusted phase settings (i.e., weights) will lead to network inferencing-accuracy losses. Unfortunately, the underlying SiPh devices in IPNNs are sensitive to inevitable fabrication-process variations (FPVs) and on-chip thermal crosstalk [2], both of which are a significant source of phase errors in IPNNs, and can cause up to 70% loss in IPNN inferencing-accuracy [3]. Leveraging the non-uniqueness of SVD under reflections, we propose a novel optimization method to improve power efficiency and robustness in SiPh-based coherent IPNNs under random uncertainties-stemming from FPVs and thermal crosstalk-without affecting the inferencing-accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…To verify this at the system-level, we consider a four-layer IPNN and observe its performance on the MNIST dataset. Each real-valued image in the MNIST dataset is converted to a complex feature vector of length 16 using a method based on fast Fourier transform [3]. A fully-connected network with two hidden layers of 16complex valued neurons is implemented using the Clements design [1].…”
Section: Introductionmentioning
confidence: 99%